Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1065
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: When assigning quantitative labels to a dataset, different methodologies may rely on different scales. In particular, when assigning polarities to words in a sentiment lexicon, annotators may use binary, categorical, or continuous labels. Naturally, it is of interest to unify these labels from disparate scales to both achieve maximal coverage over words and to create a single, more robust sentiment lexicon while retaining scale coherence. We introduce a generative model of sentiment lexica to combine disparate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…6). For predicting the sentiment labels of documents, we choose a simple procedure following Go et al (2009); Kiritchenko et al (2014); Ozdemir and Bergler (2015); Hoyle et al (2019): for each document, we replace each token with its corresponding sentiment value from a dictionary. Then, we average all values per document and pass it to a logistic regression (LR) model that is fitted on the training set to predict document labels.…”
Section: Extrinsic Evaluation: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…6). For predicting the sentiment labels of documents, we choose a simple procedure following Go et al (2009); Kiritchenko et al (2014); Ozdemir and Bergler (2015); Hoyle et al (2019): for each document, we replace each token with its corresponding sentiment value from a dictionary. Then, we average all values per document and pass it to a logistic regression (LR) model that is fitted on the training set to predict document labels.…”
Section: Extrinsic Evaluation: Classificationmentioning
confidence: 99%
“…Sentiment analysis is being applied in various domains from political science (Young and Soroka, 2012;Gründl, 2020;Widmann and Wich, 2022) to economics (Stephany et al, 2022) and computational social science (West et al, 2014;Falck et al, 2020;Stoehr et al, 2021). In all of these applications, there is a strong demand for domain-specific and interpretable methods (Hofman et al, 2021;Widmann and Wich, 2022) making dictionarybased sentiment analysis still a popular choice (Young and Soroka, 2012;Hoyle et al, 2019;Gründl, 2020;Friedrichs et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Following Hoyle et al (2019a), we use sentiment as a proxy to quantify bias, which requires a sentiment lexicon for each analyzed language. We use the combined sentiment lexicon of Hoyle et al (2019b) for English words, which was shown to outperform a number of individual sentiment lexica and their straight-forward combination on a text classification task involving sentiment analysis. Unfortunately, this is only available for English.…”
Section: Sentiment Datamentioning
confidence: 99%
“…For the remaining six languages we use Senti-VAE (Hoyle et al, 2019b) -a multi-view variational autoencoder -to combine existing sentiment lexica, the same method Hoyle et al (2019a) use to generate the English sentiment lexicon. Particularly, SentiVAE combines lexica with disparate scales into a common latent representation, where the output represents the strength of each word's sentiment (positive, negative and neutral) in the form of a three-dimensional Dirichlet distribution.…”
Section: Sentiment Datamentioning
confidence: 99%
See 1 more Smart Citation